Diversity of Natural Enemies Associated with Refuge Flowering Plants of Zinnia elegans, Cosmos sulphureus, and Tagetes erecta in Rice Ecosystem - Gracia Melsiana Aldini; Edhi Martono; Y. Andi Trisyono (Universitas Gadjah Mada, 2019)
The presence of flowering plants is essential to the conservation of natural enemies in some particular ecosystems, such as agroecosystem. The objectives of this research were to determine the natural enemies associated with refugial flowering plants Zinnia elegans, Cosmos sulphureus, and Tagetes erecta planted in the rice bunts. The research took place in the rice farms in the villages of Jatisarono, Wijimulyo, and Tanjungharjo, Nanggulan Regency, Kulon Progo, District. The natural enemies were observed using three different methods: insect nets, pitfall, and direct observation. The observations were conducted in the morning, between 07.00-10.00 a.m., with an interval twice a week for 8-weeks. The natural enemies were identified to the family level. Diversity index (Shannon-Wienner), evenness index, and dominance were calculated for each plant. The diversity index for Z. elegans, C. sulphureus, and T. erecta fell in the category of medium ranging from 1.328-1.581 with medium evenness (0.365-0.574) and high dominance of 0.314-0.453. Natural enemies associated with C. sulphureus and Z. elegans were more compared to those associated with T. erecta.